Developing the optimal chemical composition of heat-resistant Cr-Ni steel for aerospace equipment - Mishchenko, Valeriy; Kripak, Alona; Tonkonoh, Dmytro (Eastern-European Journal of Enterprise Technologies, 2023)
The object of research in this work is the processes of forming the microstructure and mechanical properties of heat-resistant steels depending on their chemical composition. The microstructure and high-temperature mechanical properties of austenitic heat-resistant chrome-nickel steels of the proposed chemical composition were investigated in the work. The microstructure study determined the grain size and topography of inclusions in steels. Based on the results of mechanical tests, a multifactorial experiment was planned, which made it possible to establish the relationship between the mechanical properties of steels with alloying elements selected as factors. The obtained regression equations were used to estimate the quantitative influence of each alloying element on the corresponding mechanical properties. Analysis of the results of the experiment made it possible to determine the optimal chemical composition of steel for gas turbine engines used in the aerospace industry, as well as in the metallurgy of titanium production. It is shown that the state of solid solution and heat-resistant niobium and molybdenum carbides (chromium carbides dissolve at a temperature of 950 °C) are an important factor that significantly affects the structure, mechanical, and service properties of heat-resistant steel. The austenite structure is provided by the required amount of nickel. The resulting indicators of heat resistance of steels of different compositions, tested at temperatures of 850 °C, 950 °C, and 1050 °C, proved the superiority of steel with a higher content of carbon and chromium and a lower content of nickel. The mechanism of steel strengthening and the influence of alloying with carbon, chromium, and nickel on it have been determined. The optimal chemical composition of heat-resistant steel on an iron-nickel basis for operation at a temperature of 950 °C has been established